Assured Deletion: A Scheme Based on Strong Nonseparability. (16th March 2022) - Xie, Zhenjie; Fu, Wei; Xu, Jianqiao; Zhu, Tingting
Abstract : Cloud storage services bring great convenience to users, but also make data owners lose direct control of their data. How to ensure that deleted cloud data can never be recovered by cloud servers or attackers is a key issue in the field of cloud storage security, which is important to protect user privacy and data confidentiality in the cloud environment. Most existing schemes have the drawbacks of overreliance on key destruction and having the ability to decrypt part of the ciphertext after cracking the key. To solve these problems, a novel cloud data assured deletion scheme based on strong nonseparability is presented. By combining XOR operation with the block cipher, the cipher data become strongly nonseparable; thus, destroying any piece of cipher data will result in unrecoverable original data. Theoretical analysis and experimental results both show that the scheme achieves the expected goals of assured deletion, which has obvious performance advantages and stronger security compared with similar schemes.